Futurism : an anthology - Rainey, Lawrence S.; Poggi, Christine, 1953-; Wittman, Laura (Yale University Press, 2009)
"In 1909, F.T. Marinetti published his first incendiary manifesto of Futurism, proclaiming, "We stand on the last promontory of the centuries!" and "There, on the Earth, the earliest dawn!" Intent on delivering Italy from "its fetid cancer of professors, archaeologists, tour guides, and antiquarians," the Futurists imagined that art, architecture, literature, and music would function like a machine, transforming the world rather than merely reflecting it. But within a decade, Futurism's utopian ambitions were being wedded to Fascist politics, an alliance that would tragically scar its reputation for decades." "Published one hundred years after the founding of Futurism, this is the most complete anthology of Futurist manifestos, poems, plays, and images ever to be compiled in English, spanning from 1909 to 1944. Now, amidst another era of unprecedented technological change and cultural crisis, is a pivotal moment to reevaluate Futurism and its haunting legacy for Western civilization."--Jacket.